Learning Academic Vocabulary: Assessing the Theoretical Impact on the Learners of English in the KRG’s Middle Schools - Omer, Talib M. (Mitanni Journal of Humanitarian Sciences, 2023)
Learning Academic vocabulary is necessary to be taught at the early stages in the middle schools. The importance of academic vocabulary only started to be discussed in 1970s (Schmitt, 2005; Hirsh, 2010; Paquate, 2010). Coxhead (2000) has collected 570 word families from different academic texts. These words cover roughly 11% of running words based on an analysis of academic texts. The knowledge of academic vocabulary is essential and needed for students of secondary or high school level. Thus, there has been concern about learners at middle schools who basically cannot understand academic textbooks or write academic texts. The aim of this paper is to review the different critical theories of the importance of the most frequent academic word list for learners in secondary schools.